Analysis of vertebral chemistry to assess stock structure in a deep-sea shark, Etmopterus spinax. (27th October 2016) - McMillan, Matthew N.; Izzo, Christopher; Junge, Claudia; Albert, Ole Thomas; Jung, Armelle; Gillanders, Bronwyn M.
Abstract : Deep-sea sharks play a valuable ecological role helping maintain food web balance, yet they are vulnerable to commercial fishing because of slow growth rates and low reproductive capacity. Overfishing of sharks can heavily impact marine ecosystems and the fisheries these support. Knowledge of stock structure is integral to sustainable management of fisheries. The present study analysed vertebral chemistry using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to assay concentrations of 7 Li, 23 Na, 24 Mg, 55 Mn, 59 Co, 60 Ni, 63 Cu, 66 Zn, 85 Rb, 88 Sr, 138 Ba and 208 Pb to assess stock structure in a deep-sea shark, Etmopterus spinax, in Norwegian and French waters. Few studies have applied this technique to elasmobranch vertebrae and the present study represents its first application to a deep-sea shark. Three stocks were identified at the regional scale off western Norway, southern Norway, and France. At finer spatial scales there was evidence of strong population mixing. Overall, the general pattern of stock structure outlined herein provides some indication of the spatial scales at which stocks should be viewed as distinct fisheries management units. The identification of an effective multi-element signature for distinguishing E. spinax stocks utilizing Sr, Ba, Mg, Zn and Pb and the methodological groundwork laid in the present study could also expedite future research into stock structure for E. spinax and deep-sea elasmobranchs more generally.